2020
DOI: 10.1111/gcb.15449
|View full text |Cite
|
Sign up to set email alerts
|

Windows of vulnerability: Seasonal mismatches in exposure and resource identity determine ocean acidification’s effect on a primary consumer at high latitude

Abstract: It is well understood that differences in the cues used by consumers and their resources in fluctuating environments can give rise to trophic mismatches governing the emergent effects of global change. Trophic mismatches caused by changes in consumer energetics during periods of low resource availability have received far less attention, although this may be common for consumers during winter when primary producers are limited by light. Even less is understood about these dynamics in marine ecosystems, where c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 57 publications
(70 reference statements)
0
24
0
Order By: Relevance
“…Such species-specific differences suggest that these co-occurring understory kelps employ distinct 'strategies' in the timing and magnitude of their resource mobilization for growth. In this system, these phenological differences in basal production may be critical to sustaining certain consumers' energetic demands during the more physiologically stressful winter season (Kroeker et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such species-specific differences suggest that these co-occurring understory kelps employ distinct 'strategies' in the timing and magnitude of their resource mobilization for growth. In this system, these phenological differences in basal production may be critical to sustaining certain consumers' energetic demands during the more physiologically stressful winter season (Kroeker et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, when understory kelp FSC was relatively high (such as during summer 2018), the relative proportion of C and N production by these species compared to giant kelp was notably increased. Prior work in this system has shown that pinto abalone (Haliotis kamtschatkana), a common rocky reef grazer, experience higher growth rates when fed a mixed algal diet consisting of several kelp species than when fed a diet of M. pyrifera alone (Kroeker et al 2021). Given that M. pyrifera dwarfed understory kelp species in terms of both FSC and productivity at sites not undergoing phase shifts, even modest increases in the relative productivity of any understory kelp species would provide a valuable, diverse source of nutrition to the primary consumer community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations